A Correlation Between Pericarpium Citri Reticulatae Volatile Components and the Change of the Coexisting Microbial Population Structure Caused by Environmental Factors During Aging - Yang, Fangqing; He, Liying; Shen, Mengyuan; Wang, Fu; Chen, Hongping; Liu, Youping (Frontiers in Microbiology, 2022)
Pericarpium Citri Reticulatae (PCR) is a natural product that is used widely in food and is an ingredient in traditional Chinese medicine. PCR improves gradually with aging. However, the present research has not yet revealed its reasons. Based on the important role of microorganisms in the aging quality formation of tobacco and fermented tea and our findings that the coexisting Aspergillus niger played an important role in the change of flavonoids and volatile oil in PCR, we put forward that “the longer storage, the better” for PCR is highly correlated with the change of the coexisting microbial population structure caused by environmental factors. Samples of PCR aged in Beijing, Sichuan, Guangdong and Yunnan were collected at different time points. Using GC/MS and high throughput 16S rRNA and ITS sequencing techniques, massive changes in volatile profile and microbial communities were observed during aging. Spearman correlation analysis indicated that Exobasidium, Xeromyces，Pseudocercospora, Russula, Aspergillus, Herbaspirillum, Sphingomonas and Streptococcus are the dominant microbial genera in Sichuan and Guangdong, showed strong connections with volatile components of chemical markers. It was preliminarily verified that the changes of volatile components for PCR is highly correlated with the change of the coexisting microbial population structure caused by environmental factors, providing a new idea for the research on the aging mechanism of PCR and key influencing factors of aging quality.